Development and characterization of functionalized TiO2-reinforced Schiff base epoxy nanocomposites. (November 2015) - Lakshmikandhan, T.; Alagar, M.
Caprolactam Schiff base epoxy (CSEp) has been synthesized and characterized by Fourier transform infrared and proton nuclear magnetic resonance ( 1 H NMR) spectroscopies. Titanium dioxide (TiO2 ) has been functionalized with 3-aminopropyltriethoxysilane (F-TiO2 ), and different weight percentages (1, 3, and 5 wt%) of F-TiO2 were reinforced with CSEp and are cured by caproamine. Thermal properties of CSEp/F-TiO2 composites were characterized using thermogravimetric analysis and differential scanning calorimetry. Data obtained from X-ray diffraction, scanning electron microscopy (SEM), and transmission electron microscopy analyses indicate the homogeneous morphology of composites. The surface morphology of ultraviolet-exposed and -unexposed samples were analyzed using SEM and compared. Results from absorption and transmittance studies infer that the F-TiO2 -reinforced hybrid composite materials offer excellent radiation-resistant behavior when compared to that of neat epoxy matrix.